2014
DOI: 10.7897/2230-8407.0512188
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antirheumatoid Arthritic Activity of Aqueous Root Extract of Clitoria Ternatea

Abstract: In ethano medicine, roots of Clitoria ternatea (Family: Fabaceae) is claimed to possess antirheumatoid arthritic activity. However, this claim has not been scientifically tested and validated yet. This study assessed the antirheumatoid arthritic potential of an aqueous root extract (ARE) of Clitoria ternatea (Family: Fabaceae) using a well recognised in vitro bioassay model: inhibition of heat induced denaturation of albumin protein, which is claimed to act as an index of anti arthritic activity. Five concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…Because in arthritic conditions autoantigens are produced due to protein denaturation, thus NSAIDs used in such conditions impair heat-induced denaturation of proteins. Therefore, the outcomes of this study confirmed the anti-arthritic potential of NA-2 formerly reported by Perveen et al (2014) (14).…”
Section: Analgesic Activitysupporting
confidence: 91%
“…Because in arthritic conditions autoantigens are produced due to protein denaturation, thus NSAIDs used in such conditions impair heat-induced denaturation of proteins. Therefore, the outcomes of this study confirmed the anti-arthritic potential of NA-2 formerly reported by Perveen et al (2014) (14).…”
Section: Analgesic Activitysupporting
confidence: 91%
“…According to Ranaweera et al [15], a well-known in vitro bioassay model to assess the anti-rheumatoid arthritic potential of an aqueous root extracted from the C. ternatea, through the inhibition of heat denaturation of the albumin protein, claimed to act as an index of anti-arthritic activity. In this study, the root extract of the C. ternatea plant was checked against a fresh hen's egg albumin, in which the results stated that the extract inhibited the denaturation of protein, which is one of the leading causes of rheumatoid arthritis.…”
Section: Anti-arthritic and Anti-inflammatory Potentialmentioning
confidence: 99%
“…Three flavonol glycosides, kaempferol-3-β-glucoside, quecetin-3-β-glucoside, and myricetin-3-β-glucoside were isolated from the petals of C. ternatea, amongst these particularly quercetin-3β-D-glucosides were identified by NMR studies, and LC/MS studies in highest quantities particularly in methanolic extracts of the C. ternatea flower petals 15 . The hydroalcoholic extracts of blue flower petal possess potential antioxidant and anti-inflammatory activities, and its disease modifying activities has been correlated to its flavonoid components 16,17,18 .…”
Section: Scheme 1: Role Of Tnfα / Tnfr1 Mediated Signaling In Inflammmentioning
confidence: 99%